"Primary" nocardial brain abscess in a renal transplant patient. (December 2015) - Weerakkody, Ranga; Palangasinghe, Dhammika; Wadanambi, Saman; Wijewikrama, Eranga
Abstract Background Intracranial abscesses are rare among transplant recipients, andNocardia is responsible for less than 2 % of them. Nocardiosis, a chronic infection and is difficult to treat. Primary infection involves lungs and eventually disseminates. Primary nocardial abscesses are rare and we report a case from Sri Lanka. Case presentation A 38 year old Sri Lankan, who has received his 2nd ABO matched live donor transplantation, which was complicated with perinephric hematoma and massive transfusion syndrome. He presented with fever, worsening headache and papilledema. An urgent magnetic resonance image (MRI) showed an occipital abscess with midline shift. Craniotomy and drainage followed by 3 week course of imipenem and levofloxacin, which rendered him symptom free. After 12 months he has stayed recurrence free. Imaging and bacteriology of the respiratory tract failed to demonstrateNocardia infection. Conclusion Isolated (Primary) nocardial brain abscess are rare, and have an excellent response to medical therapy. We achieved a good response from a relatively short course of antibiotics (not using sulfonamides, due to allergy), where long courses of antibiotic had been the norm.